Management of information, process and cooperation : third International Workshop, MiPAC 2016, Hangzhou, China, September 23, 2016, Revised selected papers /: third International Workshop, MiPAC 2016, Hangzhou, China, September 23, 2016, Revised selected papers. (2017) - Unknown
No abstract available